(untitled) (Fiep Bulletin - online, 2014)
This study derives from a precedent one regarding the use of video-analysis as an educational tool for learning the technical skills of futsal in a group of children aged 9-10 years, they practice it to competitive level. This study uses the video-analysis post-competition to motivate children to acquire psychological and social abilities, that could affect on pleasure (McAuley & Blissmer, 2002), on self-esteem and on self-efficacy (Felz, 1992). Therefore, the aim is to adopt the video-analysis in the educational process to help players to live all together in sport (Raiola, 2008). The method is the study of integrated case with experimental one, comparing the data of begin with end activity between the sample group and the control group. The data are recruited by the following instruments: the register of the boys frequencies in the sample group compared to the control group; a questionnaire on satisfaction, on self-esteem and on self-efficacy drawn up by the coach, the researcher and a parent, and technical skills test assessment in the precedent study. The results are increase of the assiduousness to the trainings (+3%); increase of the satisfaction, the self-efficacy and the selfesteem (+5%), and improvement of technical skills (+7%). The study shows the effectiveness of the use of video-analysis in the educational process and the prospective of further research involving the development system of the teaching method with the use of technologies. It would be useful in educational activities and didactic organization of a specific space to investigate the issue.